2022
DOI: 10.3390/jcm11175072
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Tubercle to Trochlear Groove Distance Measured by Posterior Condylar Reference Line on MRI Can Over-Evaluate Lateralization Deformity of Tibial Tubercle in Patients with Recurrent Patellar Dislocation

Abstract: Background: The tibial tubercle to trochlear groove (TT-TG) distance is currently considered as an indication for tibial tubercle osteotomy. While the influence of femoral condylar morphology on such measurement remains unclear. Methods: A total of 86 patients with patellar dislocation (PD) and 86 healthy individuals were enrolled. Femoral condylar morphology and the TT-TG distance measured by anatomical transepicondylar axis (TT-TGa), by surgical transepicondylar axis (TT-TGs), and by posterior condylar refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…By cross‐referencing the sagittal image, the first axial slice showing a cartilaginous trochlea was referred to assess the morphology of the trochlear entrance: a line subtended from the cartilaginous surface of the lateral trochlea (LTL) was identified. Then the MRI was scrolled distally, and the axial slice with intact posterior femoral condyles was identified to define the following marks: PCRL, the line through the sulcus of the medial epicondyle and the prominence of the lateral epicondyle (SEA), and the line through the prominence of the medial and lateral epicondyles (AEA) [28]. The angles between the LTL and PCRL, SEA, and AEA were regarded as LTIp, LTIs and LTIa, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…By cross‐referencing the sagittal image, the first axial slice showing a cartilaginous trochlea was referred to assess the morphology of the trochlear entrance: a line subtended from the cartilaginous surface of the lateral trochlea (LTL) was identified. Then the MRI was scrolled distally, and the axial slice with intact posterior femoral condyles was identified to define the following marks: PCRL, the line through the sulcus of the medial epicondyle and the prominence of the lateral epicondyle (SEA), and the line through the prominence of the medial and lateral epicondyles (AEA) [28]. The angles between the LTL and PCRL, SEA, and AEA were regarded as LTIp, LTIs and LTIa, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, clinicians have recognized that dysplasia of lateral femoral condyle (LFC) was involved in LPD. Liu et al [ 5 ] and Zhao et al [ 6 ] reported that shorter posterior LFC was associated with LPD. Yang et al [ 7 ] showed that patients with LPD had both anterior and posterior LFC deformities.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral femoral condyle ratio (LFCR) serves as a measurement on conventional radiograph (CR) to assess the length of femoral condyles [ 9 ]. Lateral femoral condyle distance (LFCD) measured by transverse computed tomography (CT) or MRI images was used to evaluate the length of LFC as well [ 6 , 10 , 11 ]. Hodel et al [ 12 ] and Vasta et al [ 13 ] elucidated that lateral femoral condyle index (LFCI) measured on sagittal MRI plane or CR could reliably evaluate the morphology of LFC.…”
Section: Introductionmentioning
confidence: 99%